Лінгвокомунікативні чинники ідентифікації нараторів у романі В. Набокова Приглашение на казнь - Бацевич, Флорій (Slavia Orientalis, 2022)
It is proved that one of V. Nabokov’s most famous novels Invitation to a Beheading is a fictional narrative with a complicated interaction of various types of story‑telling instances. There are persons of a non‑diegetic narrator, who incorporates the features of an all‑knowing and a limited teller, explicated with a different degree of definiteness; a diegetic narrator – the main hero, – who is thinking his state over, is talking to himself, is writing a letter to his wife; a non‑personalized narrator, similar to the abstract narrator in a set of traits; and a hardly definable narrator, who is telling the text story addressing the main hero in the second person and who can be identified as a non‑diegetic or a diegetic narrator talking to himself. The article defines the correlation of these indefinitely outlined story‑telling instances (convergence, binding, juxtaposition), ones identified with difficulty. Conducted is a lingual differentiation of the mentioned story‑tellers’ expression, mainly, via deictic elements (mostly, pronouns); addresses; the “historical past” and “historical present” tenses; predicates that mark the participants’ diegesis or non‑diegesis as well as various intonational and stylistic means (the expression of evaluation, diminutive or augmentative noun forms and others). It is considered perspective to attempt to classify the lingual means of expressing the types of story‑telling instances in different belles‑lettres genres, to analyze the semantic and pragmatic reasons for forming the “story” and the “discourse” of a narrative. In general, the problem of the linguistic “dimension” of narratives is a perspective direction of investigation where there can be revealed semantic and pragmatic categories of production and perception of any type of narration, firstly, belles‑lettres – fictional by dint of its deep nature.
Keywords: narration; narrative “story”; narrative “discourse”; narrator; story‑telling instance; diegesis